Metodologia de dimensionamento de plantas fotovoltáicas flutuantes em açudes do semiárido - Reges, Jonas Platini (2022)
The introduction of Floating Photovoltaic (FPV) plants in reservoirs in semi-arid regions can have the following advantages: reducing water evaporation from reservoirs, increasing the efficiency of electricity power generation due to the cooling provided by the aquatic environment, and reducing competition land use. Based on this hypotheses and by benefiting from the specific characteristics of each reservoir, a new methodology for sizing FPV plants in dams in semi-arid regions by using the duration curve of the reservoir is proposed hereby. The methodology is divided into five steps: Obtaining historical data on dams in a semi-arid region (in this case, the Brazilian and Australian semi-arid regions); construction of the duration curve referring to the flooded area of the dams; choice of reliability levels and verification of boundary conditions to determine the FPV plant area; calculation of the installed capacity of the FPV plant and daily electricity production using the daily values of local photovoltaic productivity; and calculation of the estimated daily evaporation rate and associated evaporation reduction from each weir. The methodology is innovates as it focusing on the use of reservoirs in semi-arid areas around the world, usually characterized by high variability in the level of stored water, consequently altering the flooded area. The case studies applied to reservoirs in the Brazilian semi-arid region (Nova Floresta, Thomás Osterne, Forquilha, Pentecoste and Orós) and in Australia semi-arid region (Rifle Creek, Tailings Dam, Lake Moogerah, Lake Awoong and Yarra Yarra Lakes) consider two scenarios for power generation: one with high reliability level (90%, scenario 1) and one with low reliability level (70%, scenario 2). For each scenario, two modules are adopted, 245 Wp and 275 Wp. The sum of the annual electricity generation from the FPV plants of the Brazilian dams studied can reach 5,874 GWh and 14,745 GWh, for scenarios 1 and 2, with an estimated total evaporation reduction of 62 hm3 and 157 hm3 respectively. The sum of the annual electricity generation from the FPV plants of the Australian dams studied can reach 6,053 GWh and 14,334 GWh, for scenarios 1 and 2, respectively.